The KTB apatite fission-track profiles: Building on a firm foundation?. (15th October 2015) - Wauschkuhn, B.; Jonckheere, R.; Ratschbacher, L.
Highlights: The Kontinentale Tiefbohrung reveals defects of the apatite fission-track method. Near-isothermal holding lasts since the Late Cretaceous to Palaeocene exhumation. Fossil tracks in natural apatite do not etch as induced tracks in annealed apatite. Surface-intersecting and confined fission tracks are sampled with different bias. None of the annealing models can claim decisive support from geological data. Abstract: Deep boreholes serve as natural laboratories for testing thermochronometers under geological conditions. The Kontinentale Tiefbohrung (KTB) is an interesting candidate because the geological evidence suggests that approximate isothermal holding since the last documented exhumation in the Late Cretaceous to Palaeocene is a reasonable assumption for the thermal histories of the KTB samples. We report 30 new apatite fission-track ages and 50 new mean confined track lengths determined on cores from the 4 km deep pilot hole. The ϕ- and ζ-external detector ages are consistent with the population ages from earlier studies and together define a clear age profile. The mean track lengths from this and earlier studies reveal the effects of experimental factors. The measured age and length profiles are compared with the predictions of 24 annealing models for isothermal holding. There are clear discrepancies between the measured and calculated profiles. Down to 1.5 km depth, the measured mean track lengths are shorter than the predicted. The balance of methodological evidence indicates that this is due to seasoning, i.e., a shortening of the fossil confined tracks without attendant age reduction. From 2.5 to 4.0 km depth, the mean track lengths are longer than the predictions. This suggests that the bias model that weights the probabilities of observing tracks of different length and which is based on experiments relating surface track densities to mean track lengths is not appropriate for confined tracks. Experimental and methodological factors are sometimes difficult to disentangle, but present a sufficient margin for there to be no need to go against the independent geological evidence. Unknown geological events cannot be ruled out but their existence cannot be inferred from the fission-track data alone, much less can the nature or magnitude of such events be specified.